Detailed characterization of MLH1 p.D41H and p.N710D variants coexisting in a Lynch syndrome family with conserved MLH1 expression tumors. (16th September 2014) - Pineda, M.; González‐Acosta, M.; Thompson, B.A.; Sánchez, R.; Gómez, C.; Martínez‐López, J.; Perea, J.; Caldés, T.; Rodríguez, Y.; Landolfi, S.; Balmaña, J.; Lázaro, C.; et al.
<x xml:space="preserve">Abstract</x> Lynch syndrome (LS) is an autosomal dominant cancer‐susceptibility disease caused by inactivating germline mutations in mismatch repair (MMR) genes. Variants of unknown significance (VUS) are often detected in mutational analysis of MMR genes. Here we describe a large family fulfilling Amsterdam I criteria carrying two rare VUS in the MLH1 gene: c.121G > C (p.D41H) and c.2128A > G (p.N710D). Collection of clinico‐pathological data, multifactorial analysis, in silico predictions, and functional analyses were used to elucidate the clinical significance of the identified MLH1 VUS. Only the c.121G > C variant cosegregated with LS‐associated tumors in the family. Diagnosed colorectal tumors were microsatellite unstable although immunohistochemical staining revealed no loss of MMR proteins expression. Multifactorial likelihood analysis classified c.2128A > G as a non‐pathogenic variant and c.121G > C as pathogenic. In vitro functional tests revealed impaired MMR activity and diminished expression of c.121G > C. Accordingly, the N710 residue is located in the unconserved MLH1 C‐terminal domain, whereas D41 is highly conserved and located in the ATPase domain. The obtained results will enable adequate genetic counseling of c.121G > C and c.2128A > G variant carriers and their families. Furthermore, they exemplify how cumulative data and comprehensive analyses are mandatory to refine the classification of MMR variants.